Implementasi Bot WhatsApp untuk Layanan Informasi Frontline: Studi Kasus: STMIK WICIDA - Putra, Muhammad Sadam Saktia; Azahari, Azahari; Heny Pratiwi (Universitas Methodist Indonesia, 2025)
This study implemented a WhatsApp bot as a frontline information service at STMIK Widya Cipta Dharma (WICIDA). The main problems were the high burden of repetitive questions, limited service hours, and inconsistent responses. WhatsApp was chosen because of its high adoption rate and support for real-time communication. The study included needs analysis, bot architecture design, Node.js-based development, knowledge base integration, and performance evaluation. The results showed that the bot was able to answer 87.4% of questions correctly, reduce staff workload by 56%, and speed up response time to <3 seconds. These findings demonstrate that the WhatsApp bot is effective as a scalable solution to improve the quality of educational information services.